Margaret of Anjou : tradition and revision : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Cron, B. M. (Massey University, 1999)
Introduction: The Sources A broad consensus on the political activities of Margaret of Anjou exists in the scholarship of the late twentieth century; unfortunately it continues to be influenced by the traditional view of a virago who interfered in politics and encouraged faction in Lancastrian England. There are a number of reasons for this, not least that there is no detailed scholarly study of the queen1 1 A complete list of biographies of Margaret of Anjou is given in the bibliography. cf. T.F. Tout, 'Margaret of Anjou,' for a pithy and accurate commentary on Margaret's early biographers. Dictionary of National Biography, vol. 12, London: Oxford University Press, 1917. Originally published 1893. because she has been of peripheral interest to historians of Henry VI and the Wars of the Roses, although it is generally agreed that her participation was important, perhaps crucial; that she dominated her weak and compliant husband, Henry VI, and attempted to rule England herself, preferring factional government and civil war to reconciliation and rule by a representative council of lords under the king. Margaret of Anjou is not a sympathetic character, although she is sometimes portrayed as a tragic one. She has been savaged by Shakespeare from whom there is no appeal.2 2 Henry VI Part 3, Act 1, Scene 4: The Duke of York to Margaret of Anjou: 'She-wolf of France, but worse than wolves of France, Whose tongue more poisons than the adder's tooth!' 'O tiger's heart wrapp'd in a woman's hide!' 'But you are more inhuman, more inexorable - O, ten times more - than tigers of Hyrcania.' Margaret then stabs York and orders that his head be cut off. She was on the losing side of a struggle in which her Yorkist opponents were masters of the art of propaganda. The portrait of Margaret in the Yorkist chronicles has, in the main, been accepted by English authorities. 3 Patricia-Ann Lee, 'Reflections of Power: Margaret of Anjou and the Dark Side of Queenship,' Renaissance Quarterly, 39, (Summer 1986), for a concise, but not always accurate, summary of the views of English historians. French writers are a little kinder, since Margaret was a French princess and more to be pitied than blamed for becoming the wife of Henry VI. The Burgundians are less tolerant as they were allies of Edward IV and their chronicles reflect an Anglo-Burgundian (Yorkist) rather than an Anglo-French (Lancastrian) perspective; but they display the same Yorkist gloss that colours their English counterparts. History is not kind to failure. English historians, assessing the fifteenth century from a moral and patriotic viewpoint, had no difficulty in accepting the verdict of their Tudor predecessors that Margaret was a foreign French woman who interfered in the affairs of a country she neither valued nor understood. The tradition that Margaret dominated English politics from the time of her marriage is discredited, but her part in the political clash that culminated in the Wars of the Roses is still open to debate. Was she responsible for the demise of the Lancastrian dynasty or was she a victim of circumstance as the wife of an ineffectual king, the mother of a child heir and the leader by default of those who opposed Richard of York's bid for the throne?
Keywords: Great Britain; Henry VI, 1422-1461; History; Wars of the Roses, 1455-1485; Margaret, of Anjou, Queen, consort of Henry VI, King of England, 1430-1482